Bootstrap 4 from scratch with 5 projects - Traversy, Brad (Packt Publishing, 2018)
"The author has created a completely custom HTML learning environment for the first few sections of this course. Each lecture has an HTML page associated with it and has a start state. As we move along through the lectures, you code along with me learning all that Bootstrap 4 offers including helpers/utilities, components, widgets, flexbox and more. Bootstrap Starter Pack - Once you get through the sandbox, we will setup the starter pack which I also created for this course. This will give us a real development workflow to compile Bootstrap 4 from source and compile Sass. It will even give us a dev server with autoload. This is what we will use for the 5 projects. We will use the Starter pack to create 5 real-world themes."--Resource description page